2014
DOI: 10.1037/pmu0000032
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mode and musical experience on the attribution of emotions to melodic sequences.

Abstract: The connection between emotion and music runs deep, and despite a growing body of research, the influence of musical structure on emotion perception is only partially understood. The present study examined the relationship between mode and emotion attribution, as well as how musical experience influences emotion perception. Thirty-four participants listened to sequences of musical scales and melodies consisting of randomized sequences of notes in each of the seven diatonic modes and the major-minor scale, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…Experiment 1 showed that the mode and harmonic complexity influenced the psychological perception of Western music in Chinese people. Consistent with previous studies ( Juslin and Lindström, 2010 ; Huron and Davis, 2012 ; Juslin and Sloboda, 2013 ; Parncutt, 2014 ; Straehley and Loebach, 2014 ; Lahdelma and Eerola, 2014 ; Bonetti and Costa, 2017 ), the major mode induced greater pleasure than the minor mode. Moreover, the major mode induced greater arousal and dominance than the minor mode, whereas the minor mode induced greater tension than the major mode.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…Experiment 1 showed that the mode and harmonic complexity influenced the psychological perception of Western music in Chinese people. Consistent with previous studies ( Juslin and Lindström, 2010 ; Huron and Davis, 2012 ; Juslin and Sloboda, 2013 ; Parncutt, 2014 ; Straehley and Loebach, 2014 ; Lahdelma and Eerola, 2014 ; Bonetti and Costa, 2017 ), the major mode induced greater pleasure than the minor mode. Moreover, the major mode induced greater arousal and dominance than the minor mode, whereas the minor mode induced greater tension than the major mode.…”
Section: Methodssupporting
confidence: 91%
“…The structural difference between the major mode and the minor mode produces distinct sound effects. The root of the minor triad is more ambiguous and uncertain than the root of the major triad ( Parncutt, 2014 ); therefore, the major mode tends to induce positive emotions, while the minor mode tends to induce negative emotions ( Juslin and Lindström, 2010 ; Huron and Davis, 2012 ; Juslin and Sloboda, 2013 ; Straehley and Loebach, 2014 ). For example, Lahdelma and Eerola (2014) explored the emotional perceptions of different chords (i.e., major, minor, diminished, augmented, and seventh chords) and showed that the valence ratings of the major triad were the highest.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Bruner (1990; see also Gabrielsson & Juslin, 1996; Gabrielsson & Lindström, 2001; Juslin, 2000, 2005; Juslin & Laukka, 2000, 2003) reviewed numerous studies from the fields of psychology, musicology, and marketing and summarized the various possible iconic meanings that different musical structures may have in terms of time-, pitch-, and texture-related factors. Similarly, Straehley and Loebach (2014) found that the emotional connotations of various musical modes could be captured in terms of their valence and intensity, consistent with the circumplex dimensions of pleasantness and arousal, respectively.…”
supporting
confidence: 56%
“…However, a growing body of evidence shows that music can at least express emotional meaning in a less arbitrary way (e.g. Andrade, Vanzella, Andrade, & Schellenberg, 2017;Cespedes-Guevara & Eerola, 2018;Fritz et al, 2009;Huovinen & Kaila, 2015;Juslin, 2013;Juslin and Laukka, 2003;Koelsch, 2011;Schubert, 2013Straehley & Loebach, 2014Swaminathan & Schellenberg, 2015;Tiemann & Huron, 2011). In addition, there is evidence of semantic meaning in music (e.g., Brodsky, 2011, HaCohen & Wagner, 1997Huovinen & Kaila, 2015;Koelsch et al, 2004;Margulis, 2016Margulis, , 2017Noble & McAdams, 2018), and of musical humour (Huron, 2004;Goeth, 2016).…”
mentioning
confidence: 99%